Influence of FSC certification on the governance of the logging sector in the Congo basin - Lescuyer, G.; Tsanga, R.; Nziengui, S.; Forni, E.; Romero, C. (Wiley, 2021)
The performance of private forest governance systems, such as the standard and approach developed by the Forest Stewardship Council (FSC), is often assessed at the local level although they also have an indirect influence on public policies at the national level. Such spillover effects must be understood to assess the effectiveness of certification in contributing to improved forest governance. With this purpose, this article analyses the influences of the implementation of FSC standards on changes in forest governance in Cameroon, Congo and Gabon based on perceptions of 43 “knowledgeable” actors of FSC natural forest management. The information was collected through the use of semi-open and open interviews, and rankings. Findings show that perceived FSC influence on forest governance has followed two pathways: (a) a clear impact on stakeholder participation and timber traceability; and (b) a limited impact on improving national governance, as illustrated by the lack of global improvement in resource management practices or in biodiversity conservation. Moreover, interviewees agreed that struggles against corruption and transparency have not been impacted by the FSC certification in the Congo Basin. This mitigated influence of FSC on forest governance is first explained by a limited spillover effect of the virtuous practices of the seven FSC-certified companies on the national logging sector. Secondly, progress in FSC certification has been little taken up by public policies, which remain the main leverage for action on forest governance in producing countries.